2015
DOI: 10.1615/intjmedmushrooms.v17.i9.80
|View full text |Cite
|
Sign up to set email alerts
|

A Water-Ethanol Extract from the Willow Bracket Mushroom, Phellinus igniarius (Higher Basidiomycetes), Reduces Transient Cerebral Ischemia-Induced Neuronal Death

Abstract: This study investigated the potential neuroprotective effect of a mushroom extract from Phellinus igniarius (Piwep) after transient cerebral ischemia. Ph. Igniarius, which has a history of traditional medicinal use, contains immunomodulatory compounds that have been described to have effects on the human immune system. Using a model of transient cerebral ischemia induced by both common carotid artery occlusion and hypovolemia, a water-ethanol extract precipitate of Ph. Igniarius (Piwep) was delivered intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The study used a model of transient cerebral ischemia and showed that the administered extract inhibited neuronal death in the hippocampus and prevented oxidative damage, microglia activation, and blood‐brain barrier disruption. Thus, it can be speculated that this extract has beneficial effects on stroke‐induced damage and may have high therapeutic potential in clinical conditions [44,45] . Similar results were obtained in the experiment with an ethanolic extract of P. igniarius containing numerous polyphenolic compounds.…”
Section: Phellinus Igniariussupporting
confidence: 74%
“…The study used a model of transient cerebral ischemia and showed that the administered extract inhibited neuronal death in the hippocampus and prevented oxidative damage, microglia activation, and blood‐brain barrier disruption. Thus, it can be speculated that this extract has beneficial effects on stroke‐induced damage and may have high therapeutic potential in clinical conditions [44,45] . Similar results were obtained in the experiment with an ethanolic extract of P. igniarius containing numerous polyphenolic compounds.…”
Section: Phellinus Igniariussupporting
confidence: 74%
“…A majority of medicinal mushrooms were reported to affect the nervous system namely, Lion’s Mane, H. erinaceus and Tiger Milk, Lignosus rhinocerotis . The latter two mushrooms can stimulate neurite outgrowth (Samberkar et al, 2015), whereas Phellinus igniarius can reduce transient cerebral ischemia-induced neuronal death, suppress oxidative injury and disrupt the blood–brain barrier via microglia activation (Kim et al, 2015). Agaricus blazei protects the brain against oxidative stress-induced damage and increases mitochondrial-coupled respiration (de Sá-Nakanishi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, hispolon enhanced the expression of tumor protein p53, specific silencing of which almost completely reversed hispolon-mediated antitumor activity. Additionally, a potential neuroprotective effect of an extract from P. igniarius after transient cerebral ischemia has been demonstrated [26]. The authors of one of the reports suggested that P. igniarius extract may have a high therapeutic potential for ameliorating multiple sclerosis progression [27].…”
mentioning
confidence: 99%